Polymer light-emitting devices using poly(ethylene oxide) as an electron injecting layer - Rao, M. V. Madhava; Huang, Tsung-Syun; Su, Yan-Kuin; Tu, Yan-Kuin; Huang, Chun-Yuan; Wu, Shang-Shung (Nano-Micro Letters, 2010)
The performance of polymer light emitting devices (PLEDs) based on polyvinyl carbazole (PVK) is improved by introducing a nanoscale interfacial thin layer, made of poly(ethylene oxide) (PEO), between the calcium cathode and the PVK emissive layer. It is believed that the PEO layer plays a key role in enhancing the device performance. In comparison to the device with Ca/Al as the cathode, the performance of the PLED with PEO/Ca/Al cathode, including the driving voltage, luminance efficiency is significantly improved. These improvements are attributed to the introduction of a thin layer of PEO that can lower the interfacial barrier and facilitate electron injection.